Pendampingan Baca Tulis Al-Qur’an Pada Anak Usia Dini di Desa Kotah Jrengik Sampang - Takwallo (Jurnal Insan Pengabdian Indonesia, 2023)
In Kotah village itself there are several places to recite the Koran, one of which is TPA al-Mas'udiyah. The author chose Sukamulya TPA because there are approximately 40 students, but there are only 2 ustadz and ustadzah teachers (tPA managers). Apart from that, the students' interest in studying the Koran varies, some are enthusiastic and serious, but there are also those who seem forced and lazy. Of course, as a first step, efforts that can be made to overcome this problem are to educate and instill in children from an early age a strong love for the Al-Qur'an. The author focuses on the problem formulation in this activity as: "Assistance in reading and writing the Al-Qur'an in early childhood in Kotah village, Jrengik Sampang”. This program is implemented using the method of providing materials, roleplay, games and training. It is hoped that participants can receive the material well and practice directly with the assistance of the facilitator team. Implementation includes (1) Preparation, (2) Planning learning methods, (3) Subject approach, (4) Implementation of training, (5) Evaluation. The conclusion is that the guidance and learning to read and write the Koran through the Iqra method at the al-Mas'udiyah TPA in Kotah village has been carried out well. Assistance in writing Al-Qur'an letters using a pattern where the teacher makes a hijaiyyah letter pattern and the children's task is to thicken the hijaiyyah letter pattern. This can indirectly improve the ability to read and write the letters of the Koran in the children of al-Mas'udiyah TPA, Kotah village, Jrengik Sampang.